1888
DOI: 10.1007/bf01970047
|View full text |Cite
|
Sign up to set email alerts
|

Zur Frage über die secundären Degenerationen des Hirnschenkels

Abstract: Im Jahre 1885 hatte ich in der russischen Literatur zwei Mittheilungen fiber FMle mit Degeneration der Hirnschenkelfasern verSffentlicht, in denen unter Anderem secund~ire absteigende Degeneration der ~tussersten Abschnitte des Hirnschenkelfusses oder dee sogenannten Tfirck'schen Bfindels beschrieben wurde*). Seitdem sind in der deutschen Literatur einige Mittheilungen fiber Fitlle mit secundarer Degeneration der lateralen Pattie des HirnschenkeJfasses erschienen**), durch welche meine friiher gemachten Beobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1960
1960
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The origin, extent, and termination of the temporal lobe projections to the basis pontis have long been the subject of dispute. Earlier investigations using degeneration techniques in humans showed evidence for pathways to the cerebral peduncle and termination in the pons arising from a wide variety of lesions in different parts of the temporal lobe (Bechterew, 1888;Dejerine, 1893, '01;Edinger, 1899;Flechsig, 1881;Hosel, '02;.Kam, 1895;Kattwinkle and Neumayer, '10;Kreuser, 1892;Marie and Guillain, '03;Pusateri, '07;Rhein, '11, '22;Van Gehuchten, 1896, 1897Von Monakow, 1891;Winkelman and Eckel, '29;Winkler, '27;Zacher, 1891). Not all observers were able to replicate these findings, however (Mills and Spiller, 1896;Von Brero, 1896).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The origin, extent, and termination of the temporal lobe projections to the basis pontis have long been the subject of dispute. Earlier investigations using degeneration techniques in humans showed evidence for pathways to the cerebral peduncle and termination in the pons arising from a wide variety of lesions in different parts of the temporal lobe (Bechterew, 1888;Dejerine, 1893, '01;Edinger, 1899;Flechsig, 1881;Hosel, '02;.Kam, 1895;Kattwinkle and Neumayer, '10;Kreuser, 1892;Marie and Guillain, '03;Pusateri, '07;Rhein, '11, '22;Van Gehuchten, 1896, 1897Von Monakow, 1891;Winkelman and Eckel, '29;Winkler, '27;Zacher, 1891). Not all observers were able to replicate these findings, however (Mills and Spiller, 1896;Von Brero, 1896).…”
Section: Discussionmentioning
confidence: 99%
“…Some observers have expressed doubts concerning the existence of a projection to the pons originating in the temporal lobe (Bucy and Kluver,'40;Rundles and Papez,'38). Most earlier investigators [reviewed in part by Nyby and Jansen ('51) and Sunderland ('4011 have, however, observed fiber terminations in either the rostral or caudal pons after lesions in various regions of the temporal lobe (Abbie, '34;Bechterew, 1886Bechterew, , 1888Beevor and Horsely, '02;Borowiecki, '11;Dejerine, 1893, '01; 1897,1898Flechsig, 1881;Hosel, '02;Kam, 1895;Kreuser, 1892;Levin, '36;Lowenstein, '11;Masuda, '14;Mettler, '35a;Winkler, '27;Zacher, 1891). Whereas temporopontine terminations in the ventral part of the basis pontis have been described (Sunderland,'40;Winkler,'27), the terminations in its dorsolateral or lateral parts have been more strongly emphasized (Masuda,'14;Mettler,'35a; Nyby and Jansen,'51;Sunderland,'40;Winkler,'27).…”
mentioning
confidence: 99%
“…for more details see Iioche, 1898). Bechterew (1885Bechterew ( , 1887 and Hoche (1898), on the basis of degeneration studies in human pathological specimens, concluded that these fibers, in contrast to other lemniscal fibers, were descending and Hoche (1898) named the temporal cortex as one of their possible sources of origin. This is also suggested by the presence of fibers entering the lemniscal stratum of the tegmentum from the sublenticular segment of the internal capsule shown as bundle YI by Fore1 (1877, fig. 5. j, Also in a human case with a lesion in the sylvian area, von Monakow (1895) demonstrated descending degenerating fascicles in the mesencephaiic reticular foymation.…”
Section: Temporotegrnental Tractmentioning
confidence: 99%
“…• The external stria (outer stripe of Baillarger, layer 4) was found as a second dip in the intensity profile. A third dip in the intensity profile corresponded to a Kaes-Bechterew stripe (Bechterew, 1891;Kaes, 1907) in layer 3a.…”
Section: Anatomical Interpretation Of Mri Intensity Profilesmentioning
confidence: 96%
“…Of relevance, while Berlin (1858) focused on cyto‐architecture based on neuronal staining, Meynert (1867) described different types of cortices (archipallium and neopallium) based on the lamination produced by the distribution of cell and white matter (WM; for more details, see Fulton, 1937). These remarkable advances were then complemented by myelo‐architectonic and cyto‐architectonic studies by many (Bechterew, 1891; Flechsig, 1920; Ramon y Cajal, 1909). Formal descriptions of the parcellation of the cerebral cortex followed (Smith, 1907; von Economo & Koskinas, 1925; C. Vogt & Vogt, 1919).…”
Section: Introductionmentioning
confidence: 99%